2005
DOI: 10.1007/s00466-005-0659-4
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid flow in a channel under the action of a uniform localized magnetic field

Abstract: In this work the fundamental problem of the biomagnetic (blood) fluid flow in a channel under the influence of a steady localized magnetic field is studied. For the mathematical formulation of the problem both magnetization and electrical conductivity of blood are taken into account and blood is considered as a homogeneous Newtonian fluid. For the numerical solution of the problem, which is described by a coupled, non linear system of PDEs, with appropriate boundary conditions, the stream function-vorticity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…The computational data has been compared to the numerical data taken from Tzirakis et al [1] where the fluid has been considered as Newtonian. For this simple preliminary analysis, differently from [1] where a computational mesh consists of 2000 quadrilateral elements was used, a grid of approximately 14000 elements has been found [9] to be more effective in the present study providing high-accuracy and agreement with the results of Tzirakis et al [1]. A uniform inlet velocity profile has been considered relying on [1] as well as the magnetic field strength has been taken as B 0 = 25 √ 7 T esla.…”
Section: Non-isothermal Hartmann Flow For Newtonian and Non-newtonianmentioning
confidence: 99%
See 4 more Smart Citations
“…The computational data has been compared to the numerical data taken from Tzirakis et al [1] where the fluid has been considered as Newtonian. For this simple preliminary analysis, differently from [1] where a computational mesh consists of 2000 quadrilateral elements was used, a grid of approximately 14000 elements has been found [9] to be more effective in the present study providing high-accuracy and agreement with the results of Tzirakis et al [1]. A uniform inlet velocity profile has been considered relying on [1] as well as the magnetic field strength has been taken as B 0 = 25 √ 7 T esla.…”
Section: Non-isothermal Hartmann Flow For Newtonian and Non-newtonianmentioning
confidence: 99%
“…However, the two-dimensional Hartmann flow as a first preliminary case is considered for the validation of the implemented UDFs in the ANSYS-FLUENT environment, because the flow physics is relatively simple and the size of the computational domain is small. The fully developed outlet velocity profile of the Hartmann flow compared to the computational data of Tzirakis et al [1] is shown in Figure 1. It can be seen in Figure 1 that the outlet velocity profile of a fully developed Hartmann flow is different from the fully developed velocity distribution of an incompressible laminar flow without the presence of a magnetic field as it is expected.…”
Section: Non-isothermal Hartmann Flow For Newtonian and Non-newtonianmentioning
confidence: 99%
See 3 more Smart Citations